Problem-based learning (PBL) model: How does it influence metacognitive skills and independent learning? - Vina Nopia Saputri; Aryani Dwi Kesumawardani (CV. FOUNDAE, 2021)
The problem-based learning (PBL) model creates an active and creative learning atmosphere. It is expected to positively influence students' cognitive skills and learning independence. This research aimed to determine whether the PBL model influence 1) students' metacognitive skills; 2) students' learning independence; and 3) metacognitive skills and learning independence simultaneously. This research was a quasi-experimental research with a Posttest-Only Control Group Design. This research employed the quantitative method with the cluster sampling technique. The instruments of this research were a metacognitive skill description test and a learning independence questionnaire. The research hypothesis was tested using the MANOVA test after the data had been tested for their normality and homogeneity. The results showed that the PBL model influenced 1) students' metacognitive skills; 2) students' learning independence; and 3) metacognitive skills and learning independence simultaneously. The results indicated that the PBL model produced a better result on students’ metacognitive skills and learning independence compared to the conventional learning model.